Quality of Service for the Issuance of Certificates for the First Time at the Land Office of Donggala Regency - M. Mau, Rusli; Nuraisyah, Nuraisyah; Haryono, Dandan; M, Mustainah; Suasa, Suasa (International Journal of Social Science, Education, Communication and Economics, 2024)
The purpose of this study is to Determine the Quality of Service for the First Time Certificate Issuance at the Donggala Regency Land Office. Qualitative method as the basis of the research, the object of the research is the quality of the service of the First Time Certificate Issuance at the Donggala Regency Land Office, while the research subject involves the apparatus that serves the service process as the target of analysis. Informants are selected based on the Purposive Sampling technique. Data collection is carried out through literature studies, field studies (observation and interviews), data analysis is carried out inductively through the stages of reduction, presentation, and conclusion. Based on the results of the research, the quality of the first certificate issuance service at the Donggala Regency land office is as follows: The Dimension of Precision Has Been Running Quite Effectively However, the Dimension of Speed Has Not Been Effective, the Dimension of Convenience Has Not Been Fully Effective, and the Dimension of Justice Has Not Been Fully Effective. In conclusion, the quality of the service for the issuance of certificates for the first time at the Donggala Regency Land Office has not been effective.